2015
DOI: 10.1038/srep11343
|View full text |Cite
|
Sign up to set email alerts
|

Continental drift and climate change drive instability in insect assemblages

Abstract: Global change has already had observable effects on ecosystems worldwide, and the accelerated rate of global change is predicted in the future. However, the impacts of global change on the stability of biodiversity have not been systematically studied in terms of both large spatial (continental drift) and temporal (from the last inter-glacial period to the next century) scales. Therefore, we analyzed the current geographical distribution pattern of Plecoptera, a thermally sensitive insect group, and evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…This conclusion strongly agrees with Tierno de Figueroa et al. (), and is supported by more recent studies (Conti, Schmidt‐Kloiber, Grenouillet, & Graf, ; Li et al., ; Sheldon, ), which suggested how at least 324 taxa of the European Plecoptera (62.79%) can be included in one or more categories of vulnerability to climate change by range retractions and even local extinctions. In Sierra Nevada, other strategies facing climate change are found for freshwater invertebrates.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This conclusion strongly agrees with Tierno de Figueroa et al. (), and is supported by more recent studies (Conti, Schmidt‐Kloiber, Grenouillet, & Graf, ; Li et al., ; Sheldon, ), which suggested how at least 324 taxa of the European Plecoptera (62.79%) can be included in one or more categories of vulnerability to climate change by range retractions and even local extinctions. In Sierra Nevada, other strategies facing climate change are found for freshwater invertebrates.…”
Section: Discussionsupporting
confidence: 90%
“…Freshwater insects are generally active dispersers, yet compared with other orders of freshwater insects, stoneflies are highly dispersal‐limited (Fochetti & Tierno de Figueroa, ; Graf et al., ; Li et al., ). Communities of short‐dispersing species tend to be assembled by environmental filtering at the local scale and, therefore, species‐specific patterns of ITV are critical for ensuring species survival (Kichenin et al., ; Thompson & Townsend, ; Villéger & Mouillot, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, current and future changes caused from human activities are likely to have a stronger influence on their diversity than past anthropogenic alterations [52]. Global warming especially threats the potential future distribution and persistence of the sensitive habitats used by endemic Plecoptera [13,53], even though this phenomenon was not directly considered in our study. Several studies have also shown that land use is an influential factor in determining species distribution, even though, in our study, this influence was relatively weak based on NMS.…”
Section: Influential Environmental Factors Related To the Existence Omentioning
confidence: 52%